Konflik Sosial dan Peran Media Massa (Tinjauan Buku): Social Conflict and the Role of Mass Media (Book Review) - Sukron Ma’mun (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2011)
This study examines the role of mass media in constructing the image of Muslims in Indonesia, particularly through coverage of the bloody conflicts in Poso and Maluku. Suf Kasman, the author of the reviewed book, analyzes news framing in the newspapers Kompas and Republika using framing analysis. The findings reveal that both media tended to be emotional, provocative, and not entirely objective in their reporting, thereby influencing public perception. The article also highlights the importance of media methodology for religious scholars to understand contemporary social dynamics. Penelitian ini mengkaji peran media massa dalam mengkonstruksi citra umat Islam di Indonesia, khususnya melalui pemberitaan konflik berdarah di Poso dan Maluku. Suf Kasman, penulis buku yang ditinjau, menganalisis framing pemberitaan di harian Kompas dan Republika dengan menggunakan metode analisis framing. Hasil penelitian menunjukkan bahwa kedua media cenderung emosional, provokatif, dan tidak sepenuhnya objektif dalam memberitakan konflik, sehingga memengaruhi persepsi publik. Artikel ini juga menyoroti pentingnya pendekatan metodologi media bagi ilmuwan agama untuk memahami dinamika sosial kontemporer.